705. Four Superbugs Isolated From a Single Patient in the United States: E. coli (EC) and K. pneumoniae (KP) Harboring NDM-5, P. aeruginosa (PA) Harboring NDM-1 and Candida auris. (26th November 2018) - Khan, Ayesha; Hanson, Blake; Dinh, An; Wanger, Audrey; Ostrosky-Zeichner, Luis; Miller, William; Arias, Cesar
Abstract: Background: The spread of carbapenem resistance in Enterobacteriacae (CRE) and PA is an urgent public health concern. Candida auris ( CA ) is also an emerging threat, with the epicenter of US cases on the East Coast. Transcontinental spread of multi-drug-resistant (MDR) organisms has the potential to change local susceptibility patterns via dissemination of resistance determinants or high-risk clones. Here, we report and characterize MDR-isolates of EC, KP, PA and CA, all isolated from a single patient admitted to an ICU in Houston, Texas after complications from plastic surgery in India. Methods: CRE were isolated from the urine, PA from respiratory cultures and CA from wound cultures. Antimicrobial susceptibility testing was performed on Vitek 2 or by Etest. Synergy testing was done by Aztreonam (ATM) E-test on Mueller-Hinton agar supplemented with 2.2 µg/mL avibactam. Bacterial isolates underwent whole genome sequencing on an Illumina MiSeq, and resistance determinants (Abricate using CARD), plasmid replicon types (PlasmidFinder 1.3) and sequence type (Tseemann MLSTtool) were identified. Genes were verified by PCR. Results: The CRE were resistant to all β-lactams, including ceftazidime/avibactam (CZA) and ceftolozane/tazobactam. Synergy testing with CZA+ATM reduced the ATM MICs of the EC from >256 to 0.5 µg/mL and the KP from >256 to .094 µg/mL, while the PA ATM MIC was 4 µg/mL irrespective of the presence of avibactam. WGS indicated that the EC and KP shared the bla NDM-5, bla TEM-4, and bla CTX-M-15 β-lactamase genes, as well as IncFII and IncX3 plasmid replicon types. In addition, the EC harbored bla CMY-59, bla OXA-181, qnrS1 and two additional IncB and IncY plasmid replicon types. The PA isolate harbored bla NDM-1, qnrVC1, several aminoglycoside resistance genes and a type 1 integrase. The CA isolate had a fluconazole MIC of >256 µg/mL and a micafungin MIC of 0.125 µg/mL. Conclusion: Here we report the identification of 4 MDR organisms, including the first reported isolate of CA in Houston, in one patient. The pattern of resistance determinants suggests horizontal transmission of bla NDM-5 between the CRE isolates. Prompt recognition of MDR organisms is imperative to prevent healthcare-associated spread. Disclosures: W. Miller, Merck: Investigator, Research support. C. Arias, Merck & Co., Inc.: Grant Investigator, Research support. MeMed: Grant Investigator, Research support. Allergan: Grant Investigator, Research support.